ENSURING PATIENT SAFETY IN ANESTHESIOLOGY: INTERNATIONAL STANDARDS AND NEW APPROACHES - Urunov Zokirjon Burxanovich (Modern American Journals, 2025)
Patient safety in anesthesiology and reanimatology is one of the core priorities of medicine, where international standards and emerging technologies play a pivotal role. This article provides a detailed review of international guidelines (e.g., ESAIC and ASA standards) aimed at enhancing patient safety, along with 2025 advancements such as automated monitoring systems and quality improvement programs. The work is based on scientific studies and guidelines published in 2025 and complies with the requirements of the Higher Attestation Commission of Uzbekistan (OAK), offering original analysis and practical recommendations. Results indicate that adherence to standards can reduce perioperative complications by 15–25%, though challenges persist in their practical implementation.
Keywords: patient safety, anesthesiology, reanimatology, international standards, monitoring systems, quality control.